Świadkowie przeszłości ziemi siedleckiej (biogramy): Augustynik Marek, Denisiuk Ludwik, Lipka Jan - DEMIDOWICZ, Tomasz (Historia i Świat, 2021)
Biographies of people born or related to activities in the area of Southern Podlasie and Eastern Mazovia.